Studying the Effectiveness of Some Plant Powders on the Biological Activities of the Confused Flour Beetle Tribolium confusum du Val (Coleoptera: Tenebrio-nidae). - Abuelnnor, Nagat Ali (Al-Mukhtar Journal of Sciences, 2020)
This study aims to test the biological effect of three plant powders of (black pepper fruit Piper nigrum L., nutmeg seeds Myristica fragrans Houtt and bay leaf Laurus nobilis L.) when mixed with wheat flour at concentrations of; 0.2, 0.5, 0.75, 1 and 1.5 % (w/w) against the confused flour beetle Tribolium confusum. Results showed that the black pepper fruit caused a decrease in the production of larvae that reached 65.36%, while the nutmeg seeds powder caused a decrease of 50.93% compared with the bay leaf powder, which caused a decrease of 38.20%. The results also showed a decrease in the first generation progeny (F1) that reached 90.75% and 75.34% due to the treatment with the black pepper fruit and the nutmeg seeds powders respectively. However, the bay leaf powder was less effective, with only a decrease of 30.13%.